Characterization of unusual DS‐1‐like G3P[8] rotavirus strains in children with diarrhea in Japan. Issue 5 (5th February 2018) - Komoto, Satoshi; Ide, Tomihiko; Negoro, Manami; Tanaka, Takaaki; Asada, Kazutoyo; Umemoto, Masakazu; Kuroki, Haruo; Ito, Hiroaki; Tanaka, Shigeki; Ito, Mitsue; Fukuda, Saori; Suga, Shigeru; et al.
Abstract : The emergence and rapid spread of novel DS‐1‐like intergenogroup reassortant rotaviruses having the equine‐like G3 genotype (DS‐1‐like G3P[8] strains) have been recently reported from several countries. During rotavirus surveillance in Japan in 2015–2016, three DS‐1‐like G3P[8] strains were identified from children with severe diarrhea. In the present study, we sequenced and characterized the full genomes of these three strains. On full‐genomic analysis, all three strains showed a unique genotype constellation including both genogroup 1 and 2 genes: G3‐P[8]‐I2‐R2‐C2‐M2‐A2‐N2‐T2‐E2‐H2. Phylogenetic analysis revealed that each of the 11 genes of the three strains was closely related to that of Japanese DS‐1‐like G1P[8] and/or Japanese equine‐like G3P[4] human strains. Thus, the three study strains were suggested to be reassortants that acquired the G3‐VP7 gene from equine G3 rotaviruses on the genetic background of DS‐1‐like G1P[8] strains. Our observations will provide important insights into the evolutionary dynamics of emerging DS‐1‐like G3P[8] strains.